KAJIAN KELAYAKAN OPERASIONAL RUMAH PEMOTONGAN HEWAN (RPH) OEBA PEMERINTAH KOTA KUPANG NUSA TENGGARA TIMUR DALAM MENGHASILKAN DAGING DENGAN KUALITAS ASUH - Eni Rohyati; Bernadus Ndoen; Cardial L.O. Leo-Penu (Politeknik Pertanian Negeri Kupang, 2010)
Based on the result of Rohyati,et al (2007), the RPH Oeba did not fulfill 82,78% of complex and operational requirements or only meet 19.25% to those standardsÂ in producing meat with ASUH quality (Safe, hygiene, Wholesome, and Halal). Through this article, the writer tried to analyze about the appropriate level of operational activity of RPH Oeba in meat producing with ASUH quality. Some of operational in the slaughterhouse that not fulfilled those standards are: No attention for workers hygiene and animal welfare, all operational using of non-hygiene water, using nonstandardized equipments,Â not appropriate based on Islamic rules, skinning and carcass handling were not done properly, slaughtering process was not following the direction of stream production, â€œClean and dirtyâ€ operational activities were located in the same areas, ante mortem and postmortem inspection were not done, sick animal and productive female were also slaughtered, sick animal was not isolated in quarantine pensKeywords: slouhterhouse, Oeba, meat quality